Improving Employee Performance in terms of Leadership, Remuneration, and Competence - Muhammad Taufik Lesmana; Syahriani Syahriani (International Journal of Business Economics (IJBE), 2022)
The purpose of the study was to determine and analyze the influence of leadership, remuneration, and competence on PT employees' performance. Perkebunan Nusantara III (Persero) Medan. The approach used is a quantitative research approach. The sample used in this study was 84 employees. The data analysis technique used Multiple Linear Regression. The study's results partially prove that leadership, remuneration, and competence significantly positively affect employee performance. Then simultaneously, leadership, remuneration, and competence significantly influence the employee performance of PT Perkebunan Nusantara III (Persero) Medan.